1 ANALYSIS OF THE MANAGEMENT AND DEVELOPMENT OF ENVIRONMENTAL SOCIAL ENTREPRENEURSHIP IN UZBEKISTAN - Narzullaev, Elmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The main objective of this study is analyzing and measuring the capability of improving and developing social enterprises in Uzbekistan. The theoretical basis of the scale is supported by empirical research in the social sector. On other hand, finding out both strengths and weaknesses on managing and developing environmental social entrepreneurship in our country also was our main aim in this article.